Assessment of RVACS performance for small size lead-cooled fast reactor. (March 2015) - Wu, Guowei; Jin, Ming; Chen, Jiayue; Bai, Yunqing; Wu, Yican
Highlights: The RELAP5 model of CLEAR-I RVACS was established and verified by comparison with three-dimensional CFX calculation. CLEAR-I RVACS performance was analyzed by using the RELAP5 code. The maximum heat removal capability of CLEAR-I RVACS was investigated. It is suggested that CLEAR-I RVACS had the capability to remove the CLEAR-I decay heat. Several design parameters was studied to evaluate their effect on the heat removal capability of CLEAR-I RVACS. Abstract: Reactor Vessel Air Cooling System (RVACS), adopted by China Lead-based Research Reactor (CLEAR-I), was considered as a promising solution to passively remove the decay heat under accident conditions. In order to assess CLEAR-I RVACS performance, the investigation of CLEAR-I RVACS performance has been conducted by using the RELAP5 code. The RELAP5 model of CLEAR-I RVACS was established and verified by comparison with three-dimensional computational fluid dynamics commercial code CFX calculation. The maximum heat removal capability of CLEAR-I RVACS was investigated. Several design parameters, such as presence of air cool tubes, vessel size and chimney height, have been studied to evaluate their effect on the heat removal capability. It is suggested that CLEAR-I RVACS had the capability to remove the CLEAR-I decay heat and could apply for the 25 MW pool type fast reactors as an independent decay heat removal system. The heat removal capability of the RVACS with air channel was 7.5% bigger than that of the RVACS with air tubes for the same main vessel and air thermal cycle. A 10 m increase in chimney height resulted in a 5 °C decrease in the main and safety vessel temperatures. A 10% increase in the whole size of CLEAR-I RVACS resulted in a 20 °C decrease in the main and safety vessel temperatures.